2009
DOI: 10.1194/jlr.m800400-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid transport protein 4 is dispensable for intestinal lipid absorption in mice

Abstract: FA transport protein 4 (FATP4), one member of a multigene family of FA transporters, was proposed as a major FA transporter in intestinal lipid absorption. Due to the fact that Fatp4 2/2 mice die because of a perinatal skin defect, we rescued the skin phenotype using an FATP4 transgene driven by a keratinocyte-specific promoter ( 2/2 ;Ivl-Fatp4 tg/1 mice, there was no difference in hepatic VLDL secretion in-vivo or in hepatic lipid content on either a chow or Western diet. Taken together, our studies find no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 33 publications
(46 reference statements)
4
52
0
2
Order By: Relevance
“…Although Fatp4 was previously thought to play a role in transport of fatty acids across the plasma membrane, more recent data have shown that Fatp4 is dispensable for fatty acid uptake in different cell types (5,10,11). Supporting this notion, uptake of radiolabeled fatty acids into adipose tissue in our study was undisturbed in Fatp4 AϪ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 82%
“…Although Fatp4 was previously thought to play a role in transport of fatty acids across the plasma membrane, more recent data have shown that Fatp4 is dispensable for fatty acid uptake in different cell types (5,10,11). Supporting this notion, uptake of radiolabeled fatty acids into adipose tissue in our study was undisturbed in Fatp4 AϪ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 82%
“…Overexpression studies have often led to different conclusions concerning effectors of fatty acid influx due to changes in protein levels and cellular location (6,31,32), and as such, we have focused our efforts on loss of function models. Our initial studies confirmed a major role of FATP1 in facilitating insulin-stimulated fatty acid uptake, whereas silencing of FATP4 had little influence on basal or insulin-stimulated fatty acid uptake (6).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, consistent with the insulin-stimulated translocation of FATP1 to the plasma membrane ( 5 ), FATP1 is required for insulin-stimulated LCFA uptake ( 3,5 ). Functional studies of FATP4 have shown that the protein does not play a role in LCFA uptake in either enterocytes ( 23 ) or adipocytes ( 3 ) but in fat cells may function in fatty acid reesterifi cation following lipolysis ( 3 ).…”
mentioning
confidence: 99%